TLX1 and NOTCH coregulate transcription in T cell acute lymphoblastic leukemia cells - Riz, Irene (BioMed Central, 2010)
BACKGROUND: The homeobox gene TLX1 (for T-cell leukemia homeobox 1, previously known as HOX11) is inappropriately expressed in a major subgroup of T cell acute lymphoblastic leukemia (T-ALL) where it is strongly associated with activating NOTCH1 mutations. Despite the recognition that these genetic lesions cooperate in leukemogenesis, there have been no mechanistic studies addressing how TLX1 and NOTCH1 functionally interact to promote the leukemic phenotype. RESULTS: Global gene expression profiling after downregulation of TLX1 and inhibition of the NOTCH pathway in ALL-SIL cells revealed that TLX1 synergistically regulated more than 60% of the NOTCH-responsive genes. Structure-function analysis demonstrated that TLX1 binding to Groucho-related TLE corepressors was necessary for maximal transcriptional regulation of the NOTCH-responsive genes tested, implicating TLX1 modulation of the NOTCH-TLE regulatory network. Comparison of the dataset to publicly available biological databases indicated that the TLX1/NOTCH-coregulated genes are frequently targeted by MYC. Gain- and loss-of-function experiments confirmed that MYC was an essential mediator of TLX1/NOTCH transcriptional output and growth promotion in ALL-SIL cells, with TLX1 contributing to the NOTCH-MYC regulatory axis by posttranscriptional enhancement of MYC protein levels. Functional classification of the TLX1/NOTCH-coregulated targets also showed enrichment for genes associated with other human cancers as well as those involved in developmental processes. In particular, we found that TLX1, NOTCH and MYC coregulate CD1B and RAG1, characteristic markers of early cortical thymocytes, and that concerted downregulation of the TLX1 and NOTCH pathways resulted in their irreversible repression. CONCLUSIONS: We found that TLX1 and NOTCH synergistically regulate transcription in T-ALL, at least in part via the sharing of a TLE corepressor and by augmenting expression of MYC. We conclude that the TLX1/NOTCH/MYC network is a central determinant promoting the growth and survival of TLX1(+ )T-ALL cells. In addition, the TLX1/NOTCH/MYC transcriptional network coregulates genes involved in T cell development, such as CD1 and RAG family members, and therefore may prescribe the early cortical stage of differentiation arrest characteristic of the TLX1 subgroup of T-ALL.